2013
DOI: 10.1097/acm.0b013e318299f3e3
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Empathy to Medical Students

Abstract: These findings suggest that educational interventions can be effective in maintaining and enhancing empathy in undergraduate medical students. In addition, they highlight the need for multicenter, randomized controlled trials, reporting long-term data to evaluate the longevity of intervention effects. Defining empathy remains problematic, and the authors call for conceptual clarity to aid future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
215
1
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 491 publications
(232 citation statements)
references
References 62 publications
8
215
1
8
Order By: Relevance
“…The inference that state empathy can be taught or learned in relation to professional practice (Alligood, 1992) is supported empirically by evidence for empathy-enhancing programs with nursing and medical students (Batt-Rawden, Chisolm, Anton, Flickinger, 2013;Brunero, Lamont, & Coates, 2010). In a review of empathy education in nursing, Brunero et al (2010) found 11 out of 18 studies reported statistically significant increases in empathy as a result of empathy education.…”
Section: Empathy: State and Traitmentioning
confidence: 95%
“…The inference that state empathy can be taught or learned in relation to professional practice (Alligood, 1992) is supported empirically by evidence for empathy-enhancing programs with nursing and medical students (Batt-Rawden, Chisolm, Anton, Flickinger, 2013;Brunero, Lamont, & Coates, 2010). In a review of empathy education in nursing, Brunero et al (2010) found 11 out of 18 studies reported statistically significant increases in empathy as a result of empathy education.…”
Section: Empathy: State and Traitmentioning
confidence: 95%
“…Traditional educational efforts may no longer be considered worthy of attention and resources. Current research into empirically supported strategies for teaching empathy, for example, might become less of a priority, or even abandoned (Ançel 2006;Batt-Rawden et al 2013;Kidd and Castano 2013;Trothen 2016;Vanlaere et al 2012). Moral bioenhancements may help motivate us to be more self-reflexive and altruistic.…”
Section: Concluding Summary: Seeing Moral Bioenhancements From An Intmentioning
confidence: 99%
“…We embrace educational strategies, for example, with the goal of changing and shaping us, including our moral selves. We are developing cutting-edge forms of moral bioenhancements, and we are also developing cutting-edge educational means of moral enhancement (Ançel 2006;Batt-Rawden et al 2013;Kidd and Castano 2013). Both moral enhancement modes could potentially be used to help us to be who we want to be, and help improve the world.…”
Section: Choosing Authenticallymentioning
confidence: 99%
“…8,9 Two recent systematic reviews conclude that it is possible to teach empathy. 10,11 This paper explores the challenges of teaching empathy by interrogating various facets of the construct.…”
Section: Complexitymentioning
confidence: 99%